Numerical simulation of electron cyclotron current drive characteristics on EAST - 韦维 丁伯江 张新军 王晓洁 李妙辉 孔二华 张磊 (Chinese physics B, 2014)
Electron cyclotron current drive （ECCD） will be applied in the EAST tokamak during its the new campaign. In order to provide theoretical predictions for relevant physical experiments, some numerical simulations of ECCD with the parameters of EAST have been can＇ied out by using TORAY-GA code based on the understanding of ECCD mechanisms. ECCD efficiencies achieved in different plasma and electron cyclotron （EC） wave parameters are given. The dependences of ECCD characteristics on EC wave injection angle, toroidal magnetic field, plasma density, and temperature are presented and discussed.